ПОМОГИТЕ ПОЖАЛУЙСТА!!!!!!

Решите через один вариант - т. е сначала а. потом б пропускаете и решаете в и так далее.

1

Ответы и объяснения

Лучший Ответ!
2013-03-07T05:19:30+00:00

1 вложение

1) 

а) у= x^4, x0=-1

y ' = 4 x^3

y ' (-1)=4*(-1)=-4

в)y=-3cosx + 2sinx, x0=π/4

y ' =-3*(-sinx) + 2cosx=3sinx+2cosx

y ' (π/4)=(3√2) / 2 + √2 = (4 *√2) / 2 = 2√2

2)

a) y=4x^3*x^4=4*x^7

y ' = 28*x^6

в) y = 1 / (7x^6)=(1/7) * x^(-6)

y ' = (-6/7) * x^(-7)

3)

a) y=x^4 - 2x - 1/x

y ' = 4*x^3 - 2 +1/(x^2)

в) y = (x^5 - 2x^2 - 1)/x = x^4 - 2x - 1/x

y ' = 4*x^3 - 2 +1/(x^2)

4)

y = x * tg x

y ' = 1*tgx + x*(1/cos^2 x)

2 вложение

2) 

a) y=x^5 * (1+x)^2

y ' = 5x^4 * (1+x)^2 + 2*(1+x) * x^5 = (1+x) * (5x^4 * (1+x) + 2x^5) = (1+x) * (5x^4 + 5x^5 + 2x^5)=

= (1+x) * (5x^4 + 7x^5) , дальше упростишь сам

в) y = x*sinx

y ' = sinx + x*cosx

д) y = x^2 * sinx

y ' = 2x*sinx + x^2 * cosx

ж) y = √x * sinx

y ' = 1/2*(1/√x) * sinx + √x*cosx

и) y = (cosx+2sinx) * (2cosx - sinx)

y ' = (-sinx + 2cosx) * (2cosx - sinx) + (-cosx-2sinx) * (cosx+2sinx)=(2cosx - sinx) ^2 - (cosx+2sinx)^2

3)

a) y = (2x+3)/(3x+2)

y ' = (2(3x+2) - 3(2x+3))/(3x+2)^2=(6x+4 - 6x - 9)/((3x+2)²)=-5/((3x+2)²)

в) y = (x²-3)/(x²+3)

y ' = (2x(x²+3) - 2x(x²-3))/(x²+3)²=(2x³+6x-2x³+6x)/(x²+3)²=12x/(x²+3)²

д) y = sin x  / (x²+1)

y ' = (cos x * (x²+1) - 2x*sinx) / (x²+1)² = (x²*cosx + cosx - 2x*sinx)/(x²+1)²

ж) y = sin x / (1+cosx)

y ' = (cosx *(1+cosx) - (-sin²x))/(1+cosx)²= (cosx *(1+cosx) + sin²x)/(1+cosx)²

и) y = ctg x / (sinx+cosx)

y ' = ((-1/sin²x) * (sinx+cosx) - (cosx - sinx) * ctg x)/(sinx+cosx)²